2005
DOI: 10.1016/j.ejheart.2004.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐discharge B‐type natriuretic peptide predicts early recurrence of decompensated heart failure in patients admitted to a general medical unit

Abstract: Background: B-type natriuretic peptide (BNP) represents a promising predictor of early (30 days) re-admission in patients with heart failure (HF) admitted to cardiology units. Whether BNP retains its predictive value in unselected patients admitted to general medical wards is unknown. Methods: We determined BNP levels on admission and pre-discharge in 100 consecutive patients (71 male, mean age 78F10 years) admitted to a general medical unit due to decompensated HF. Follow-up after discharge was 30 days. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 32 publications
4
21
0
1
Order By: Relevance
“…This has been reported previously both in the hospital [6][7][8][14][15][16] as well as in the ambulatory setting [17][18][19]. Our data confirm these findings, showing that NTproBNP three months after discharge is a better prognostic marker than NT-proBNP at discharge.…”
Section: Discussionsupporting
confidence: 82%
“…This has been reported previously both in the hospital [6][7][8][14][15][16] as well as in the ambulatory setting [17][18][19]. Our data confirm these findings, showing that NTproBNP three months after discharge is a better prognostic marker than NT-proBNP at discharge.…”
Section: Discussionsupporting
confidence: 82%
“…These data also apply to NT-proBNP [52,53]. There is also substantial data indicating that elevated predischarge BNP and NT-proBNP levels portend increased morbidity and mortality after admission for ADHF [54,55]; this also applies to those with multiple comorbidities [56]. One large review of this prognostic data showed that an increase in BNP of 100 pg/ml was associated with an approximately 35% increase in the relative risk of death [45].…”
Section: Bnp and Congestive Heart Failurementioning
confidence: 92%
“…Our study was not retailed to define the prognostic impact of each comorbidity but it is well known that renal failure, anemia and cognitive deficit are the worse prognostic factors of HF in an elderly population. 21,23 Also BNP or NT pro-BNP are powerful prognostic markers: above all their discharge values are good predictors of hospital readmission, [33][34][35] but their determination was uncommon in our study.…”
Section: Discussionmentioning
confidence: 99%